(untitled) (Research, Society and Development, 2021)
The present investigation aims to carry out a correlational study between the constructs of organizational support (OS), work-related harm (DRT) and quality of life (QL) in the context of Brazilian employee health in the areas of psychology and physiotherapy. 228 workers from public and/or private organizations participated in the research, through answers to the Organizational Support Perception Scale (EPSO), Work-Related Injury Assessment Scale (ADRT) and Quality of Life Scale (Medical Outcomes Study36. SF- 36), in addition to informing sociodemographic data through the google forms electronic solution. Data analysis was performed using the statistical program SPSSWIN - version 24.0. The results revealed that the OS influences in a negative and significant way, only the DRT variable and its respective dimensions (physical, psychological, social). Regarding QoL, the findings of specific domains were low and not significant. The originality of the article lies in the approach to a scientific gap, since other studies do not explore the importance of the existence and/or absence of perception of the OS in the researched public and has as managerial implications the indication of the need for multidisciplinary intervention programs, with the objective of prevention, diagnosis and promotion of workers’ health.